Assessment of stream sediments pollution by potentially toxic elements in the active mining area of Okpella, Edo State, Nigeria (Rudarsko-geološko-naftni zbornik, 2019)
An active gold mining area in Okpella, Edo State, Nigeria was studied to assess the contribution of gold mining to the concentrations of potentially toxic elements (PTEs) in stream sediments. Standard geochemical sampling and sample treatment techniques were employed, and samples were analysed using the energy dispersive X-ray fluorescence (XRF) method. The concentrations of arsenic (As), cobalt (Co), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn) were determined in fifteen stream sediment samples from an active gold mining area, which also  receives discharged marble mine water. The enrichment factor (EF) and geoaccumulation index (Igeo) were calculated using the XRF analysis results to assess the level of PTE pollution in the area. The sediments showed a PTE concentration trend of Cu > Zn > Pb > As > Cr > Hg > Ni > Co. The EF results revealed extremely severe enrichment of Hg, moderate enrichment of Cu, minor enrichment of As and Pb, and no enrichment of Co, Cr, Ni and Zn in the sediments. The Igeo also showed that the sediments were extremely polluted with Hg, moderately polluted with Cu but there was no evidence of pollution from other PTEs. Extreme pollution of the sediments by Hg and its enrichments in Cu, As and Pb are due to indiscriminate active artisanal gold mining in the area. It is recommended that immediate remediation measures should be enforced to mitigate the possible environmental health hazards to humans and livestock in the area.